Analisis Faktor-Faktor yang Mempengaruhi Keputusan Konsumen dalam Mengajukan Kredit Motor pada PT. Nusantara Surya Sakti Bandar Lampung - Mitrawan, Andri; Anugrah, Angga (Jurnal Enterpreneur dan Bisnis (JEBI), 2022)
This research was conducted by slovin. The sample used in this research is PT. Nusantara Surya Sakti. Methods of data analysis using multiple linear regression analysis to determine the factors that influence consumer decisions as cultural factors, social factors, personal factors and psychological factors in applying for a loan bike on PT. Nusantara Surya Sakti.Based test for normality, multicollinearity test and test heteroskedastis not found any deviation from the classical assumption. of the results of F test showed variable cultural factors, social factors, personal factors and psychological factors together significantly influence consumer decisions in applying for a loan bike on PT. Nusantara Surya Sakti. This means that any changes in the independent variables are cultural factors, social factors, personal factors and psychological factors simultaneously will jointly influence the consumer's decision to apply for credit in T test motors and variable cultural factors, social factors, personal factors and psychological factors positive and significant impact on the consumer's decision to apply for credit / financing motorcycle at PT. Nusantara Surya Sakti.